2022
DOI: 10.21037/jtd-21-1851
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of secondary pneumothorax with interstitial lung disease: the surgical indications at the start of treatment is important

Abstract: Background: Secondary pneumothorax with interstitial lung disease (ILD) is often difficult to treat in comparison to primary pneumothorax. The purpose of this study was to analyze the actual management and outcome, and to find the most effective treatment.Methods: Among 180 patients with pneumothorax caused by ILD, who were managed between January 2000 and April 2021, 129 patients were included. Fifty-one patients with observation only were excluded. In the present study, a patient was considered to be cured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…In fact, surgery for pneumothorax in patients with background diseases such as ILD results in death in 4%-21% cases. 3,4 On the other hand, as a long-term prognosis can be expected if the surgery is safely completed, VATS with local anaesthesia becomes a saviour. This procedure can deal with peripheral lung and pleural lesions, which are visible without requiring strong lung compression.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, surgery for pneumothorax in patients with background diseases such as ILD results in death in 4%-21% cases. 3,4 On the other hand, as a long-term prognosis can be expected if the surgery is safely completed, VATS with local anaesthesia becomes a saviour. This procedure can deal with peripheral lung and pleural lesions, which are visible without requiring strong lung compression.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgery should be sought in cases of persistent air leakage, 6 it tends to be avoided for pneumothorax with IP because of the possibility of causing acute exacerbation of IP 23,24 . However, previous reports indicated that surgery could be performed safely in such cases 25 . Pleurodesis, which is recommended as an alternative treatment in cases where surgery cannot be performed, 1,6 also has the risk of acute exacerbation of IP and has a higher rate of the recurrence of pneumothorax than surgery 25 .…”
Section: Discussionmentioning
confidence: 99%
“…23,24 However, previous reports indicated that surgery could be performed safely in such cases. 25 Pleurodesis, which is recommended as an alternative treatment in cases where surgery cannot be performed, 1,6 also has the risk of acute exacerbation of IP and has a higher rate of the recurrence of pneumothorax than surgery. 25 Therefore, these treatment choices should be made with careful consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…本症例では第17病日に気胸を合併したことで呼吸状態が悪化し,胸腔ドレーン留置の追加および治療期間の延長を要した。薬剤性肺障害と気胸の関連性やその頻度について,明確な報告はない。一方,薬剤性を含む間質性肺炎と続発性気胸に関しては,発生率が12.9~20.2%という報告がある 10)。また,患者自身の吸気努力によって肺障害を生じる,自発呼吸関連肺障害(patient self–inflicted lung injury: P–SILI)の概念が浸透してきているが,本患者ではリザーバーマスクでの酸素投与を要する呼吸不全が長期間続いており,強い呼吸努力によりP–SILIが起きていた可能性がある。さらに一色らは,間質性肺炎の治療経過中に気胸を合併した症例群について後方視的に検討し,ステロイドが投与されている場合は気胸が難治性となりやすいと報告している 11)。本症例において,胸腔ドレーン抜去まで2週間を要した原因として,ステロイドの影響も考えうる。…”
Section: 考  察unclassified